Analysis of the Role of the Kontras Institution in Advocating for Cases of Human Rights Violations in the City of Medan - Muhammad Taufik Rahman; Hudalah Husni; Sri Rahayu Putri (Kampret Journal, 2024)
This research examines the role of the Kontras Institution in advocating for cases of human rights violations in the city of Medan, Indonesia. Through a mixed-methods approach incorporating qualitative and quantitative analysis, the study explores the organization's activities, challenges, and impact on human rights advocacy in Medan. Data was collected through interviews with key stakeholders, document analysis, and surveys administered to residents of Medan. The findings reveal that the Kontras Institution plays a crucial role in documenting human rights abuses, providing legal support to victims, and raising public awareness about human rights issues in Medan. However, the organization faces challenges such as limited resources, political pressure, and security threats, which hinder its effectiveness. Despite these challenges, the Kontras Institution has had a significant impact on human rights advocacy in Medan, contributing to increased awareness, improved access to legal aid, and greater accountability for perpetrators. The research concludes with recommendations for strengthening human rights advocacy in Medan, including increasing resources and support for organizations like the Kontras Institution and addressing systemic issues that perpetuate human rights violations. Overall, this research provides valuable insights into the role of the Kontras Institution and informs efforts to promote justice and accountability for victims of human rights violations in Medan and beyond.